Cell proliferation and apoptosis in gastric cancer and intestinal metaplasia - Forones,Nora Manoukian (2005)
BACKGROUND: Higher proliferation is commonly observed in cancer cells. Apoptosis can be a useful measure of a tumor cell kinetic. Alteration of the balance between proliferation and apoptosis is associated with cancer. AIM: To study proliferation and apoptosis on gastric cancer and in intestinal metaplasia. METHODOLOGY: Twenty-two samples from gastric adenocarcinomas and 22 biopsies from intestinal metaplasia were studied. The apoptotic bodies in hematoxylin-eosin slides and the expression of p53, bcl-2 and Ki67 were determined by immunohistochemistry. RESULTS: The number of the apoptotic cells was higher in cancer. Ki 67LI increased from intestinal metaplasia to gastric cancer. p53 was positive in 68% of the patients with cancer, more frequently in advanced stage and negative in samples of intestinal metaplasia. Although there was no significant difference between the groups, bcl-2 was positive in 45% of gastric cancer tissue and in 68% of metaplasia. In gastric cancer patients bcl-2 was expressed in early gastric cancer more frequently than in advanced stage. CONCLUSION: The positivity of bcl-2 was higher in metaplasia and probably is involved in the progression of carcinogenesis. p53 was negative in metaplasia and positive in more than half of the gastric cancer, mostly in stage IV, suggesting a late event in gastric cancer.